Duodenal Stenosis: A Case Report - Cindy Gisella Zahrany; Farahdina Shahnaz; Muzal Kadim (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Congenital duodenal stenosis in pediatric patients was often underreported due to its non-conspicuous signs and symptoms. Diagnosing duodenal stenosis is often challenging as this disease causes partial intestinal obstruction and thus presents with more indolent and atypical clinical manifestations. This case report aims to describe the atypical case of pediatric duodenal stenosis which presented with recurrent vomiting and poor weight gain as well as highlight some of the diagnostic challenges. Case: A 7-month-old girl was admitted to the emergency room with chief complaint of recurrent vomiting in the last 2 days prior to hospital admission. Patient had a history of recurrent bilious vomiting at the age of 3 days old with a frequency of 3-4 times a day and were admitted to the hospital for 2 weeks. Parents also reported of poor weight gain in the last 3 months. Abdominal X-Ray series showed dilatation of the small intestines immediately after pylorus and stack of coins sign. Esophageal endoscopic evaluation showed signs of severe GERD with a pyloric gap as well as a suspicion of a duodenal web Discussion: Congenital obstruction at the duodenum may occurs due to intrinsic or extrinsic etiology. Failure of duodenal re-canalization during the 8-10th week of embryological development is thought to be the main cause of intrinsic duodenal obstruction (atresia, stenosis or duodenal web). The appearance of clinical manifestation of duodenal stenosis depends on the degree of stenosis itself. Conclusion: Congenital duodenal stenosis may present with atypical presentations in neonates which requires clinicians to be fully aware of this diagnosis to ensure timely therapy. The main management of duodenal stenosis is surgery, however fluid administration, decompressing as well as other supportive treatment are equally crucial to ensure better outcome for the patient.